Aurora_Australis_V1_2017_Hobart_to_Davis - Walch, M (Devonport, Tasmania, 2020)
This work was made during the voyage south to undertake the 2017 Australian Antarctic Arts Fellowship at Mawson Station in Antarctica. The project extends earlier research into time-lapse visualisation begun during the ARC funded Derwent Project. It did this through the application of a time-lapse camera, fixed to the perpetually moving platform of an ice-breaker, whilst recording the traverse of the ship across the southern ocean and through the sea ice, from Hobart, Tasmania to Davis Station in East Antarctica.